Avaliação da ciclabilidade das cidades brasileiras - César, Yuriê Baptista (2014)
The growing number of cyclists pedaling in Brazilian cities demand an effort of local governments to develop actions to make their cities more bicycle friendly. However, these actions have been carried out without a plan that ensures the necessary priority to bicycle mobility. Thus, this study sought to evaluate how much the Brazilian cities are bicycle friendly, its cyclability. The relief, climate, urban aspects, pollution, integration of cycling with public transport, the quality of roads, safety, cycling infrastructure and government actions of Brazilian cities were evaluated through an online questionnaire answered by 2,925 people throughout Brazil. The survey results presented in this work show a good picture of the current situation of cyclability in Brazil: lack quality of infrastructure, lack of comfortable roads, lack of security and lack of government commitment to bicycle mobility to change this reality.